Justifiable conduct : self-vindication in memoir - Goode, Erich (Temple University Press, 2013)
How do memoirists make their work interesting, daring, exciting, and unorthodox enough so that they attract an audience, yet not so heinous and scandalous that their readers are unable to empathize or identify with them? This book explores the different strategies memoirists use to "neutralize" their alleged wrongdoing and fashion a more positive image of themselves for audiences. The author examines how writers, including James Frey, Susan Cheever, Roman Polanski, Charles Van Doren and Elia Kazan, explain, justify, contextualize, excuse, or warrant their participation in activities such as criminal behavior, substance abuse, sexual transgressions, and political radicalism.